E122Q rhodopsin: pigment microspectrophotometry, photoreceptor light responses, and bleaching adaptation - Christopher J. Meredith; Annabelle N. Tran; Alapakkam P. Sampath; Gordon L. Fain; Rikard Frederiksen (Journal of Comparative Physiology A, 2026)
When the rhodopsin visual pigment of vertebrate rods absorbs light, photoisomerization of its 11- cis retinal chromophore to all-trans retinal triggers a conformational change, ultimately leading to the formation of metarhodopsin II (meta II), the active signalling state. Meta II initiates the phototransduction cascade, culminating in membrane hyperpolarization. To investigate how meta II lifetime shapes the rod photoresponse, we studied a knock-in mouse expressing E122Q rhodopsin, a mutant pigment with a shortened meta II lifetime. Microspectrophotometry confirmed that E122Q rhodopsin is blue-shifted in its absorbance spectrum and exhibits significantly faster meta II decay than wild-type (WT). Patch-clamp recordings revealed that this shortened lifetime had little effect on response kinetics or on the dominant time constant of recovery after bright flashes. However, following pigment bleaching, rods expressing E122Q showed markedly greater desensitization than WT, indicating that free E122Q opsin activates the phototransduction cascade more efficiently in darkness. To our knowledge, this is the first report of a rhodopsin mutation that alters free opsin-driven activation of phototransduction. Given that many disease-causing mutations affect dark adaptation, such opsin-based mechanisms may be more common than previously appreciated.